1992
DOI: 10.1037/0022-006x.60.5.793
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between psychosocial functioning and body fat in preschool children: A longitudinal investigation.

Abstract: This study examined whether preschool children differed on measures of psychosocial functioning both cross-sectionally and longitudinally. One hundred and thirty-two children who varied in levels of body fat participated in the study along with their natural parents. Results indicated that the children did not differ in levels of self-esteem and family functioning as a function of their body fat. Prospectively, physical self-esteem weakly (but significantly) correlated with body fat at 1 and 2 years, and fathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 23 publications
1
35
0
1
Order By: Relevance
“…C. Strauss, Smith, Frame, & Forehand, 1985), low athletic self-concept (Braet et al, 1997;Phillips & Hill, 1998), and low physical-appearance self-concept, or low body esteem (Hill, Draper, & Stack, Mendelson & White, 1982Mendelson, White, & Mendelson, 1996;Phillips & Hill, 1998;Pierce & Wardle, 1993). In addition, obesity preceding adolescence has been associated with lower global self-concept during adolescence (R. S. Strauss, 2000), and increases in degree of overweight have been associated with decreases in athletic self-concept and global self-concept among children (Kolody & Sallis, 1995).A notable body of research, however, has failed to identify an association between childhood overweight and self-concept (Klesges et al, 1992;Mendelson et al, 1996;Rumpel & Harris, 1994;Wadden, Foster, Brownell, & Finley, 1984). In a comprehensive review of the literature, Friedman and Brownell (1995) concluded that inconsistencies in the literature are a byproduct of the simplistic approach adopted by research to date, including the search for main effects and the failure to assess factors that moderate (i.e., risk and protective factors) or mediate (i.e., reactions by peers and significant others) the relationship between weight status and selfconcept.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C. Strauss, Smith, Frame, & Forehand, 1985), low athletic self-concept (Braet et al, 1997;Phillips & Hill, 1998), and low physical-appearance self-concept, or low body esteem (Hill, Draper, & Stack, Mendelson & White, 1982Mendelson, White, & Mendelson, 1996;Phillips & Hill, 1998;Pierce & Wardle, 1993). In addition, obesity preceding adolescence has been associated with lower global self-concept during adolescence (R. S. Strauss, 2000), and increases in degree of overweight have been associated with decreases in athletic self-concept and global self-concept among children (Kolody & Sallis, 1995).A notable body of research, however, has failed to identify an association between childhood overweight and self-concept (Klesges et al, 1992;Mendelson et al, 1996;Rumpel & Harris, 1994;Wadden, Foster, Brownell, & Finley, 1984). In a comprehensive review of the literature, Friedman and Brownell (1995) concluded that inconsistencies in the literature are a byproduct of the simplistic approach adopted by research to date, including the search for main effects and the failure to assess factors that moderate (i.e., risk and protective factors) or mediate (i.e., reactions by peers and significant others) the relationship between weight status and selfconcept.…”
mentioning
confidence: 99%
“…A notable body of research, however, has failed to identify an association between childhood overweight and self-concept (Klesges et al, 1992;Mendelson et al, 1996;Rumpel & Harris, 1994;Wadden, Foster, Brownell, & Finley, 1984). In a comprehensive review of the literature, Friedman and Brownell (1995) concluded that inconsistencies in the literature are a byproduct of the simplistic approach adopted by research to date, including the search for main effects and the failure to assess factors that moderate (i.e., risk and protective factors) or mediate (i.e., reactions by peers and significant others) the relationship between weight status and selfconcept.…”
mentioning
confidence: 99%
“…In these community samples of children, excess weight appears to be primarily associated with negative perception of the child's own body, or specific psychopathology relating to eating, shape and weight (21,31).…”
Section: Introductionmentioning
confidence: 99%
“…Data from clinical and community samples show that neither being obese nor being overweight is associated with high levels of depression or anxiety (O'Neil and Jarrell 1992;Stunkard and Wadden 1992) or poor self-esteem (Kimm et al 1991;Klesges et al 1992). …”
mentioning
confidence: 99%